Zernûcî'nin Tûsî'ye Eğitim Açısından Etkisi Üzerine Bir İnceleme (Talîmü'l-müteallim fî tarîki't-teallüm- Âdâbu'l-müteallimîn Örneği) - (:unkn) unknown (My University, 2015)
XII. yüzyıl Hanefî fıkıh âlimi olan Zernûcî, Talîmü'l-müteallim adlı eseriyle ün kazanmıştır. İslam eğitim tarihinde etkileri açısından oldukça önemli olan bu eserin Zernûcî'den bir sonraki asırda yaşayan çok yönlü bir İranlı âlim ve filozof olan Tûsî'yi de etkilediği anlaşılmaktadır. Bu araştırmanın konusunu Talîmü'l-müteallim ile çoğunluk tarafından Tûsî'nin eseri olarak bilinen Âdâbu'l-müteallimîn adlı eserlerin karşılaştırması oluşturmaktadır. Karşılaştırma sonucunda Âdâbu'l-müteallimîn'in,Talîmü'l-müteallim adlı eserin mezhepçi bir bakış açısıyla gözden geçirilmek suretiyle kaleme alınmış hali olduğu ortaya çıkmıştır

Zernuci is a scholar on Hanefi law at 12th century and he had became famous with his important study named Talîmu'l-muteallim. This study is very important because of its effects on Educational History of Islam and it is understood that it has also effected Persian scholar and philosopherTûsî who lived in following century. This article is on comparison between Talîmu'l-muteallim and Âdâbu'l-muteallimîn which is known as study of Tûsî. As result of the comparison, it is seen that Âdâbu'l-muteallimîn is revised version of Talîmu'l-muteallim by the sectarian perspective
Examining Zernuci's Effect on Tûsî in terms of Education (Cases of Talîmu'l-muteallim fî tarîki't-teallum - Âdâbu'l-muteallimîn)
Keywords: Din Bilimi